2022
DOI: 10.1039/d1cp04591a
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic differences in the conformational equilibria of chalcogen-bridged compounds: the case of diallyl ether versus diallyl sulfide

Abstract: The conformational landscape of diallyl ether (DAE) and diallyl sulfide (DAS) were investigated for the first time using rotational spectroscopy from 6–20 GHz supported by quantum mechanical calculations. A significant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This work has shown that CREST, a recently introduced tool for isomer searches in computational chemistry, successfully identifies low energy isomers of chiral tag complexes. This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low‐energy isomers of weakly bound complexes 50,51,77–93 . Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high‐confidence determination of the analyte absolute configuration.…”
Section: Discussionsupporting
confidence: 72%
“…This work supports the emerging consensus from the rotational spectroscopy community that CREST is a highly successful method for identifying the low-energy isomers of weakly bound complexes. 50,51,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Further, geometry optimization using dispersion corrected DFT gives chiral tag complex equilibrium geometries with sufficient accuracy to make a high-confidence determination of the analyte absolute configuration.…”
Section: Discussionmentioning
confidence: 99%